Couple identity patterns of Tehrani women: A qualitative study - Negar Sadat Mirkazem; Masomeh Esmaeili; kosar dehdast (مجله علوم روانشناختی)
Background: Proper formation of the couple's identity is an essential condition for stability of a desirable marriage. Couple identity is culture-dependent and can take many forms and have different consequences based on various factors such as the way the couples cooperate. Despite importance of this topic, research seldom has been conducted to identify couple identity patterns in Iranian culture. Aims: This study aimed to identify the couple identity patterns among women in Tehran. Methods: The current research was conducted with a qualitative approach using Glaser’s grounded theory method in Tehran (2022-2023). The sample included 16 married women in Tehran, who were selected through purposive sampling (theoretical type). The data were collected through in-depth and semi-structured interviews, and then the data were and analyzed using Glaser’s method in three steps: open coding, axial coding, and selective coding. Results: In the present study, four patterns of women's couple identity were identified: cooperative, self-seeking-consoling, self-sacrificing and undeveloped identity. Each of these patterns are different from each other based on the characteristics of the following five axes: manifestation of the couple's personal identity, communication space, supportive-emotional space, power sharing space, and consequences. Conclusion: The results of the study demonstrate that due to the balanced contribution of the relationship parties in the collaborative couple identity pattern, this pattern can be considered the ideal relationship pattern as compared to the other patterns. It is recommended that the findings of this study be made available to experts in the field in order that they can guide couples towards the desired marital identity and improve the quality of marital relationships through education and therapy.